Hydrolyzing Proficiency of Keratinases in Feather Degradation - Gupta, Sonali (Springer India, 2014)
The keratinase degrade highly rigid, cross linked structural polypeptides with different efficiency depending on the type of source. Two newly isolated strains of Bacillus subtilis (RSE163 and RSE165; NCBI Accession no JQ887983 and JQ887982) were found to be efficient keratinase producers with unusual catalytic activity result in different morphological changes in degradation pattern of feather, confirmed by their scanned electron micrographs. Maximum keratinolytic activity of both the strains B. subtilis RSE163 and RSE165 were found to be 366 ± 15.79 and 194 ± 7.26 U after 72 h of incubation. While the disulphide reductase activity of RSE163 and RSE165 estimated 0.24 ± 0.05 and 0.15 ± 0.03 U/ml of enzyme after 24 h of incubation. A total of 16 free amino acids of variable concentration were also analyzed in the cell free supernatant of hydrolyzed feather from two strains. Present study demonstrates the action of two different keratinases in feather degradation. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s12088-014-0477-5) contains supplementary material, which is available to authorized users.